The Nandi County Political Code of Conduct - Nandi Kaburwo Council of Elders (My University, 2012)
In April 2012, more than a year before Kenya’s 2013 elections, the Nandi Kaburwo Council of Elders in Nandi Hills undertook the original task of writing the Nandi County Political Code of Conduct (NCPCC). Throughout Kenya, the pre-election period was characterized by a significant involvement of councils of elders in spreading messages of peace and promoting “good leadership”, unlike 2007 when these councils played an active role in mobilizing Kenyans to take part in the post-electoral violence. Printed as an 8-page booklet, the NCPCC was targeting local candidates, their supporters and political parties. It displayed regulations aimed to contribute to the “transformation of Nandi County” into a prosperous place, an “island of new politics, free of political madness.” Inspired from the role models of the Kenyan “Goodwill Ambassadors” for peace put in place in 2012, and based on oral narratives about iconic pre-colonial Nandi leaders—such as Kimnyolei and Koitalel Samoei—, this code of conduct brings to light cultural, social, economic and political dynamics mobilized by a wide range of actors (NGO, elders, candidates, entrepreneurs) during electoral times.
Transcript Nandi County. The Political Code of Conduct A political Code of conduct to govern and regulate all political activities within Nandi County. Preamble WE THE PEOPLE OF NANDI COUNTY: REALISING the opportunities presented to us by devolved system of governance; AWARE of the past and current political challenges; IN COMPLIANCE with the constitution of Kenya and all other relevant Laws and regulations APPRECIATING our unique challenges as a county; DETERMINED to establish our county on a strong foundation; CONSIDERING the impact of politics on the overall development of our society; COMMITTED to adopt a culture of issue-oriented politics; RECOGNISING the role of God towards achievement of our shared vision; DO HEREBY give unto ourselves this Political Code of Conduct and undertake to jealously safeguard it. 1. Background Many professions especially in the fields of healthcare, finance and legal services have codes of conduct for their members. Voters and taxpayers who elect politicians to office and pay their salaries should be able to feel confident that their elected officials will exercise fiduciary and moral responsibility while serving their counties. The power the politicians wield with its Machiavellian potential for corruption, and abuse demands that they be held to an even higher standard political code of conduct. The elected leaders therefore should be people of unquestionable backgrounds who can be relied to spearhead strategic decisions affecting the counties. In 2007 Kenya was on fire as the civil war threatened to bring the country on its knees. The post-election violence as it’s famously referred to, was caused by a disputed electoral results in the country’s general election. The Kriegler commission identified various aspects of electoral systems that required attention. These electoral malpractices make it impossible to have a free and fair election, which is a cardinal principle of democracy. Some of the malpractice that needs to be addressed includes hate speech, voter bribery, intimidation, campaign violence, discrimination, negative ethnicity, etc. A written political code of conduct provides clear ethical guidelines for everyone in the political arena. A formal code also serves to let aspiring candidates know that the county residents have high expectations of its leaders and instills confidence in the Nandi County’s professional standards and performance. A political code of conduct is one way of committing the leadership of the county to free and fair elections and the respect to the rule of law. Failure to comply with the code can often result in the disciplinary action. For a long time the government in power has been using state resources to intimidate voters and scare opposition figures keen to bring change in the governance of the country. These systematic controls of state resources including the police have had devastating governance problems witnessed today, which can be attributed to our independence constitution. With the coming to force the new constitution, which has far reaching institutional reforms in the running of the government with wider public participation in the governance processes, there is significant need for promoting citizen participation in election of leaders who will occupy both county and national level leadership positions in order to make devolution of power a reality. 2. Regulations and Commitments All Party Leaders and Political Aspirants shall append their signatures on a copy of this Code as a sign of their commitment to protect and abide by it. All political aspirants shall abide by all the laws, rules and regulations of Kenya relating to elections and the maintenance of public order. All Political Parties and political aspirants shall at all times uphold the rights and freedoms of the Nandi people as guaranteed by law. All Political Parties and political Aspirants shall have the right and freedom to put forward their views to the electorate without any hindrance subject to the relevant laws and regulations. All Political Parties and political Aspirants shall fully cooperate with the Police in any investigation and processes of enforcement of the relevant laws, rules and regulations. No Political Party and/or political Aspirant shall use state apparatus including state owned print and electronic media to the advantage or disadvantage of any other candidate for purposes of an election. All Political Parties and/or political Aspirants shall desist from the use of state vehicles, or other public resources for any electioneering campaigns or any other party business. All Political Parties and/or political Aspirants shall not engage in acts of violence or intimidation of any kind, as a way of demonstrating its strength or supremacy. All Political Parties and/or political Aspirants shall accordingly publicly condemn any form of political violence or intimidation. All Political Parties and/or political Aspirants shall desist from the use of any defamatory derogatory and insulting attacks on rival individual personalities through any form of communication, verbal or written. All Political Parties and/or political Aspirants shall take all necessary steps to coordinate their campaign activities in such a way as to avoid holding rallies, meetings, marches or demonstrations close to one another at the same time. All Political Parties and/or political Aspirants shall ensure that any clash on the date, venue or timing is resolved amicably by themselves or through their appointed representatives. All Political Parties and/or political Aspirants shall desist from any acts that may lead to breach of peace or Public Order. All Political Parties and/or political Aspirants shall where necessary in the public interest; notify the police and other relevant authorities of their public rallies and meetings in any particular area. All Political Parties and/or political Aspirants shall desist from any act that may disrupt the activities of another Political Party or Aspirant. All Political Parties and/or political Aspirants shall take charge of the activities of its supporters and advise them accordingly. All Political Parties and/or political Aspirants shall instruct their supporters that no arms or any object that can be used to cause injury shall be brought to a political rally, meeting, march, demonstration or any other political function. All Political Parties and/or political Aspirants shall respect and promote affirmative action and shall endeavor to accord a favorable campaign platform to women, people with disabilities and minorities. All Political Parties and/or political Aspirants shall avoid any discrimination based on tribe, sex, marital status, healthy status, ethnic or social origin, color; age, disability religion, conscience, belief culture, dress, language or birth in connection with election and political activity. All Political Parties and/or political Aspirants shall not knowingly give false promises to the electorate of Nandi County with a view of winning votes. All Political Parties and/or political Aspirants shall at all times cooperate fully with election officials in the performance of their lawful duties, in order to ensure peaceful and orderly elections. All Political Parties and/or political Aspirants shall conduct themselves in a peaceful manner during voting and instruct their respective supporters to do so. All Political Parties and/or political Aspirants shall instruct its supporters that no weapon or any object that can be used to cause injury shall be brought to the polling station, and that no party attire, colors symbol, emblem or other insignia shall be worn to polling station on Election Day. All Political Parties and/or political Aspirants shall extend all necessary heip and cooperation to law-enforcement agents for purposes of censuring the safety and security of election officials and party agents on polling day. All Political Parties and/or political Aspirants shall instruct their agents in attendance at polling stations to perform their duties in accordance with the electoral laws and regulations, and to cooperate fully with the election officials for the efficient, transparent and uninterrupted conduct of the elections. All Political Parties and/or political Aspirants undertake to accept the results of elections conducted in a free, fair and peaceful environment and if aggrieved will seek legal redress and not resorting to violence. All Political Parties and/or political Aspirants shall not engage in any act of voter bribery or intimidation. All Political Parties and/or political Aspirants shall not engage in any form of electoral malpractice as provided for under the relevant laws of Kenya. The reference to Political Parties and/or political Aspirants in this Code shall where applicable refer to their supporters too. The Political Parties and/or political Aspirants shallprimarily be liable for the acts of its supporters. 3. Compliance and Enforcement Registered parties and candidates bound by the Code are expected to promote the goal of the Code, publicize the Code. All Political Parties and Political Aspirants are expected to comply with this Code, to instruct candidates, office bearers and agents and members and supporters to comply with it, and with electoral laws, and to take steps to ensure that ah so instructed comply with it. Candidates shall have joint conventions to campaign. Contravention of the Code is an offence and a person convicted is liable to a fine or to imprisonment for a term determined by the Kenyan Elections Act and other Relevant Laws. There shall be a public monitoring and enforcement committee comprising of nominees from the Political Parties and other stakeholders to oversee compliance with the Code. The public monitoring and enforcement committee shall make appropriate recommendations to the Chief Electoral Officer for further action. The chief electoral officer may institute proceedings in court against offenders to enforce compliance and the courts have a range of sanctions at their disposal. The Courts may; Impose a formal warning. Shame the candidates. Impose the forfeiture of candidate deposits. Prohibit or limit the use any public media, the holding of public events, entering any voting district to campaign, the display billboards, placards or posters, the publication or distribution of campaign literature or the receiving funds from the State or foreign sources. Exclude access to voting stations. Suspend the candidate from campaigning for a period of one to two months Cancel the number of votes cast in favor of a person or party. Disqualify candidates. Recommend to registrar of political parties the cancellation or de- registration of a party. Conclusions The purpose of this code of conduct is to consolidate the relationship between citizens and policy-makers by setting out, at county level, ethical principles approved by the elected representatives. Stressing that elected representatives carry out their duties within the framework of the law and in accordance with the mandate given to them by the electorate and that they are accountable to the whole of the county population, including those electors who did not vote for them. Considering also that respect for the electorate’s mandate goes hand in hand with respect for ethical standards and deeply concerned by the increase in the number of judicial scandals involving political representatives who have committed offences while in office and noting that local and regional elected representatives are not above such offences and convinced that the promotion of codes of conduct for elected representatives will allow trust to be built up between local and regional politicians and citizens. We the undersigned representatives of the political parties hereby collectively subscribe to this code of conduct. Name ………… Post ………… Polling Station ………… Date ………… Definition: Code of conduct means ‘a set of rules of behavior for political parties and their supporters relating to their participation in an election process, to which the parties ideally will voluntarily agree; and which may subsequent to the agreement be incorporated in law.”
Keywords: local elite; SOCIAL SCIENCES::Social sciences::Political science; Council of Elders